Nonlinear control techniques for electro-hydraulic actuators in robotics engineering - Guo, Qing, 1981-; Jiang, Dan, 1980- (Boca Raton : CRC Press, 2017)
"Nonlinear Control Techniques for Electro-Hydraulic Actuators in Robotics Engineering meets the needs of those working in advanced electro-hydraulic controls for modern mechatronic and robotic systems. The non-linear EHS control methods covered are proving to be more effective than traditional controllers, such as PIDs. The control strategies given address parametric uncertainty, unknown external load disturbance, single-rod actuator characteristics, and control saturation. Theoretical and experimental validations are explained, and examples provided. Based on the authors' cutting-edge research, this work is an important resource for engineers, researchers, and students working in EHS."--Provided by publisher.
chapter 1 Introduction / t chapter 5 Output Feedback Control Method / Cheng Guan -- chapter 6 Parametric Adaptive Control Method.
Keywords: Actuators; Robotics -- Equipment and supplies; Nonlinear control theory; Hydraulic machinery